Pemanfaatan Teknologi Informasi Pada Desa Wisata di Indonesia: A Systematic Literature Review - Ibnu Ananda (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Information technology (IT) has become an important part of an organization to grow and develop in an era of disruption. IT is one of the main programs for organizations using digital transformation. Digital transformation has attracted the attention of various groups, such as academics to the Ministry of Villages, Development of Disadvantaged Regions and Transmigration of Republic of Indonesia. Abdul Hakim Iskandar Minister encourages the acceleration of transformation in tourist villages to keep up with the current era developments, so it is interesting to know how IT in tourist villages in Indonesia. The research was conducted to determine the use of IT in tourist villages in Indonesia at this time. This will show how the tourist village uses IT to provide new information, services, and value to customers. This research was conducted using a systematic literature review method. Data collection was obtained through literature studies with the topic of IT in tourist villages in Indonesia from 20 previous studies. This study analyzes and synthesizes previous research and is classified into two categories. The grouping consists of 1) the intended use of IT and 2) IT, which is used in tourist villages. The findings are 4 IT use purposes and 3 TI used in tourist villages.